1969
DOI: 10.2307/4593730
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Two Therapies for Gonorrhea

Abstract: Results indicated that gonorrhea can still be effectively treated by a single intramuscular injection of a sufficiently large dose of fast-acting penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1971
1971
1974
1974

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Although erratic absorption can be overcome somewhat by administering large and frequent doses, clinical experience has shown that few patients can be relied on to take all the tablets -or capsules prescribed. The need for an injectable antibiotic as an alternative to penicillin intramuscular therapy has been presented in earlier works (9,10). The results of this study clearly indicate that carbenicillin therapy for gonorrhea in men is effective.…”
Section: Discussionsupporting
confidence: 55%
“…Although erratic absorption can be overcome somewhat by administering large and frequent doses, clinical experience has shown that few patients can be relied on to take all the tablets -or capsules prescribed. The need for an injectable antibiotic as an alternative to penicillin intramuscular therapy has been presented in earlier works (9,10). The results of this study clearly indicate that carbenicillin therapy for gonorrhea in men is effective.…”
Section: Discussionsupporting
confidence: 55%